Investigating the effects of plasma-activated water on E. coli with the novel application of single-cell impedance flow cytometry - Brayden Myers; Rita Agus; Bilal Bouharrak; Fabio Avino; Ivo Furno (Scientific Reports)
Abstract Single-cell impedance flow cytometry (IFC) is a rapid, label-free diagnostic capable of resolving the dielectric properties of individual cells. Here, single-cell IFC is employed to investigate the effects of plasma-activated water (PAW) on E. coli. This diagnostic makes use of the frequency-dependent dielectric response of cells. By recording the dielectric spectra of E. coli, the subcellular dielectric properties can be estimated. Following exposure to PAW, significant shifts in the phase angle of the impedance of E. coli were observed compared to untreated populations. The phase shift increased with frequency and when cells were exposed to PAW with higher concentrations of reactive species. A reduction in the amplitude of the impedance signal was also noted, corresponding to a decrease in cell volume. After signal calibration with stationary-phase E. coli and a three-shell dielectric model, a sensitivity analysis and genetic algorithm were used to find the relevant subcellular dielectric parameters. The results show that the conductivity of the outer membrane, periplasm, and cytoplasm change considerably in response to PAW treatment. This indicates that PAW modifies multiple layers of the cell simultaneously and that the inactivation pathway of PAW-treated E. coli is likely not confined to a single subcellular layer. For the first time, this study demonstrates that single-cell IFC can extract meaningful and detailed information about the cellular response to plasma treatment in an efficient and label-free manner. This establishes it as a promising diagnostic for uncovering the mechanisms of a variety of biological applications of low-temperature plasmas.